Sleep problems in breast cancer survivors 1–10 years posttreatment. Issue 3 (16th May 2017) - Lowery-Allison, Amy E.; Passik, Steven D.; Cribbet, Matthew R.; Reinsel, Ruth A.; O'Sullivan, Barbara; Norton, Larry; Kirsh, Kenneth L.; Kavey, Neil B.
ABSTRACT: Objective: Sleep can affect quality of life (QoL) during cancer survivorship, and symptoms related to poor sleep can be exacerbated. We examined the prevalence, severity, and nature of subjective sleep complaints in women surviving stage I–III breast cancer who were 1–10 years posttreatment. We also examined the demographic, medical, physical, and psychosocial correlates of poor sleep in these women in order to identify the subgroups that may be most in need of intervention. Method: A total of 200 patients at a comprehensive cancer center who were 1–10 years posttreatment for primary stage I–III breast cancer with no evidence of disease at the time of enrollment completed a battery of questionnaires on demographics, sleep, physical symptoms, mood, cancer-specific fears, and QoL. Results: The women had a mean age of 57 years ( SD = 10.0), with a mean of 63.3 months ( SD = 28.8) of post-cancer treatment. Some 38% of these patients were identified as having poor-quality sleep. Women with poor sleep took longer to fall asleep, had more awakenings, and acquired 2 hours less sleep per night than those with good sleep. They also had a lower QoL, greater severity of pain, more concerns about health and recurrence, and increased vasomotor symptoms ( p < 0.05). Daytime sleepiness and depression were found to be not significantly correlated with sleep quality. Significance of results: Many breast cancer survivors had severe subjective insomnia, and several breast cancer survivor subgroups were identified as having members who might be most in need of sleep-improvement interventions. Addressing physical symptoms (e.g., vasomotor symptoms and pain) and providing education about the behavioral, social, environmental, and medical factors that affect sleep could result in substantial improvement in the life course of breast cancer survivors.